IMPLEMENTASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PADA KLINIK VALERIE BEAUTY - Maissy P. Babar; Mardhalia Saitakela (Universitas Boyolali, 2019)
Valerie Beauty Clinic is a beauty care services company. The problem that arises is that even though the customer is still recorded in the recipe book, Valerie Beauty Clinic still has difficulty in providing information, products, schedule changes, changes in schedule services, events, or the latest things to customers. This problem occurs because all customers remain systemically unregulated. Another problem that arises is that all beauty products have not been recorded in a computerized database, this is what causes difficulties in conducting product data searches. Furthermore, customers also cannot do clients or suggestions and also good dissatisfaction because of the unavailability of media. If this is allowed to continue, customers can just go to another salon. The purpose of creating a website at the Valerie Beauty Clinic is to provide satisfying services to customers through a CRM (Customer Relationship Management) strategy by looking at existing problems. The methodology that will be used is conducting interviews, observations and literatures. With the existence of a website-based system with the implementation of CRM, it can facilitate customers and clinics in providing information, products, changes in schedule services, events, or the latest things to customers, computerize all products and provide clients with complaints or suggestions online. Your data is stored in accordance with our privacy statement.